The comparison of selected methods for muscle flexibility development - Schneider, M.; Frcová, Z.; Gurín, D. (Slovak Journal of Sport Science, 2020)
The aim of this pilot experiment was to compare the effect of resistance training (rt) versus static stretching (ss) on hamstring flexibility. Study was conducted on 18 volunteers (n=18), cadet hockey players with average age 14y. Hamstring flexibility was measured by thomayers test and both active and passive range of motion (rom) of hip joint. After prestesting mentioned parameters, volunteers were randomized to rt group (n= 10) and ss gorup (n= 8). Both groups were given 2 hamstring exercises, perfmored in full rom. After 6 weeks of following exercise protocol, both groups were tested. Then four- week training pause was implemented, with pretesting players afterwards. Volunteers were swapped to another group, exercising for next 6 weeks. Last measurements were done at the end. All players improved significantly in both active and passive hip flexion, ignoring the methods. Both methods noticed improvements in every measurment, however, not all of them were statistically significant. Results of ss group were superior to st group. The ss group noticed significant changes in every observed parameter, except for active flexion of the left hip. The st group observed significant changes in passive flexion of the right hip, both active and passive flexion of the left hip. Results show, that resistance training might be beneficial for improving hamstring flexibility of young hockey players. Major limitation of this study were the sample size and duration of experiment. More research needs to be done to confirm or disprove our results.